PERSPEKTIF HUKUM REGULASI PENGGELOLAAN SAMPAH DI KABUPATEN TULUNGAGUNG - Retno Sari Dewi; Surjanti Surjanti; Widowati Widowati; Intan Permata Sari (Legal Standing : Jurnal Ilmu Hukum, 2021)
The impact of changes in human behavior and lifestyle in disposable consumption, which eventually gives birth and causes various types or variouskinds of waste including plastic packaging waste, packaging waste made of leador/stenlis, B3 waste which will have a long-term impact and be harmful to theenvironment and also public health, from the above problems make a basicdescription of the birth of a Regional Regulation which has the name Tulungagung Regency Regional Regulation Number 19 of 2010 concerning Waste Management. Which of these regulations will be used as a control, legal umbrella and regulations and used to reduce the number of waste generation in Tulungagung Regency, but what is the relationship or correlation between the Law of the Republic of Indonesia Number 32 of 2009 concerning Environmental Protection and Management, whether they have similarities or differences, or whether they collide according to the Hierarchy of Laws-Invitations or do not collide with the Hierarchy of Laws. Therefore, a study and literature review is needed to find out about this relationship. The formulation of the problem taken by the author as a study material is the first regarding the juridical review of Article 18 and Article 20 of the Tulungagung Regency Regional Regulation Number 19 of 2010 concerning waste management by Law-Law of the Republic of Indonesia Number 32 of 2009 concerning Protection and Management of the Environment and the second concerning the form of efforts to revive the implementation of the Article regarding community participation and also the Article on the provisions for disposing of waste From there, the results of the discussion and conclusions will be presented later.